Synthesis of 3‐Acetoxyoxindole Derivatives by Metal‐Free PhI(OAc)2‐Mediated Oxidation of 3‐Substituted Indoles. Issue 33 (24th October 2016) - Wang, Liang; Qu, Xing; Fang, Lizhu; Li, Zhan; Hu, Siqian; Wang, Feng
Abstract : A new metal‐free PhI(OAc)2 ‐mediated oxidation for the synthesis of 3‐acetoxyoxindole derivatives using easily available indoles as starting materials has been developed. This protocol allows efficient access to various densely functionalized 3‐acetoxyoxindoles in moderate to good yields. The experimental results demonstrate that both the electronic properties of the N ‐protecting groups of the indoles and also the acidic reaction medium play important roles in this process. Abstract : A new metal‐free PhI(OAc)2 ‐mediated oxidation for synthesis of 3‐acetoxyoxindole derivatives using easily available indoles as starting materials has been developed. This protocol allows efficient access to various densely functionalized 3‐acetoxyoxindoles in moderate to good yields.